The Application of Sharia Promotion Strategies through Direct Marketing and Word of Mouth on Consumer Purchase Intentions: A Case Study of Myrooms Printing Pekanbaru - Azzuhdi, Muhammad Fikri; Fatma, Nur Aini; Hanum, Siti Lathifa; Rinaldi, Afdhol; Juita, Risa (MUI Kota Pekanbaru, 2024)
This study aims to analyze the promotional strategies implemented by Myrooms Printing Pekanbaru in increasing consumer purchasing interest through direct marketing and word of mouth marketing approaches based on sharia values. This study uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews, and documentation. The results indicate that Myrooms Printing utilizes social media platforms such as WhatsApp and Instagram for online promotion, as well as direct approaches to consumers as part of offline promotion. Word-of-mouth marketing has proven to significantly contribute to increased customer loyalty and the attraction of new customers. From a sharia economics perspective, the promotional strategies implemented align with the principles of honesty, fairness, transparency, and avoiding excessive profit-taking. Affordable pricing strategies and good customer service also play a key role in increasing consumer purchasing interest. This study recommends that other micro-enterprises integrate Islamic values into their promotional practices to build sustainable and blessed businesses.